The Relationship Between Critical Thinking and Problem--Solving Skills Among Vocational College Technical Students - Khairul, Eillya; Mustafa M.Z., (Online Journal for TVET Practitioners, 2024)
This study examines the relationship between critical thinking and problem-solving skills among technical students at Vocational Colleges. Using a descriptive survey research approach with a questionnaire instrument, the study sample consisted of 271 final-year technical students from Batu Pahat Vocational College, Johor, and Kuantan Vocational College, Pahang. The data obtained was analyzed using Statistical Package for Social Sciences (SPSS) software using Pearson's mean score, percentage, and correlation. The results of the analysis show that there is a positive relationship between critical thinking and problem-solving skills among Vocational College technical students. This study aims to justify the research hypothesis. The implication of this study is the importance of strengthening critical thinking and problem-solving skills in the curriculum and teaching strategies to prepare Vocational College technical students to become more competent and adaptive individuals in facing the challenges of a complex and changing world. It is hoped that the results of this study can significantly contribute to the development of technical and vocational education and provide guidance for preparing a more effective curriculum to cultivate both skills among Vocational College technical students.